Hands-on machine learning on Google cloud platform : implementing smart and efficient analytics using Cloud ML Engine /: implementing smart and efficient analytics using Cloud ML Engine. (2018) - Ciaburro, Giuseppe; Ayyadevara, V. Kishore; Perrier, Alexis
No abstract available